National vigor and international silence: The background and development of Japanese sociology of education. (March 2021) - Aizawa, Shinichi
This article addresses topics related to Japanese sociology of education over the past three decades. The main academic interests of Japanese sociology of education have been educational choice and socialization in secondary education, topics also discussed in Durkheim's masterwork, L'Évolution pédagogique en France . The interests of Japanese researchers in the sociology of education were aroused because of drastic changes in the youth labor market in the mid-1990s and national curriculum reforms influenced by international educational evaluation, such as the Programme for International Student Assessment, in the 2000s. Though the number of empirical studies has increased substantially over the past two decades, this field must make efforts to develop its theoretical sophistication in order to connect to worldwide research on sociology of education.